Perancangan Aplikasi Pencarian Bengkel Mobil Dengan Implementasi Algoritma Location Based Service Di Kota Bengkulu - Rois Almunthaza; Diana Diana; Dedy Abdullah; Yulia Darmi (UNIVED Press, 2024)
Vehicles are a means of transportation used by everyone, vehicles also often experience problems so they must be repaired or serviced. Bengkulu City currently, there is no special application that provides complete and accurate information services about car repair shops in Bengkulu City. Therefore, it is important to design and develop a car repair shop search application that utilizes Location-Based Service (LBS) technology in Bengkulu City. The problem is how to make a location based service algorithm design system in Bengkulu City for the search for car repair shops. So this study is intended to design a location-based service algorithm system in Bengkulu City about searching for car repair shops using a system that can be used on mobile phones with the Android operating system. By utilizing mobile technology and Location-Based Service (LBS) in finding the nearest auto repair shop from their location by providing information about the repair shop name, address, telephone number, customer reviews, and possibly other useful information, such as operating hours or special services provided by the repair shop. So when going to service the vehicle we simply use the application through the handhone. The results showed that the design of a location-based service algorithm in Bengkulu City for car repair shop search can help car service sellers to promote superior products to be sold, produce a combination of GPS features in determining the starting point and can display information search for workshop names and workshop locations based on latitude and longitude.